(untitled) (Scientific journal of the Fergana State University, 2023)
The scientist of the early Renaissance, the genius Abu Nasr Farabi, revived ancient Greek philosophy, enriched it with new philosophical theories and conclusions, created Eastern Muslim philosophy. Farabi studied the origins of ancient Greek culture with the help of the works of such philosophers as Aristotle, Plato, Ptolemy. He also studied the culture of the peoples of Sogd, Khorasan, the Sassanid state, the Kushan state among nomadic tribes. The thinker created a unified and logically complete philosophical thinking. He based it on a person and his creative activity. Man as the cause of all creatures created by God, His behavior manifests itself in the mind inherent only in humanity. The question of cognitive activity of scientific, philosophical and spiritual-moral views of the thinker is discussed in connection with the point of view of achieving happiness by a person. The importance of studying, analyzing and implementing the views highlighted in the teachings of Abu Nasr Farabi is scientifically substantiated as the main goal of building a renewing society in Uzbekistan and the process of educating a harmonious personality. This article describes the expression of knowledge in the philosophy of Abu Nasr Farabi. We can see his pantheistic views in the theoretical analysis of reason.